2021
DOI: 10.1111/ijfs.15483
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the quality and in vitro digestibility of brown rice noodles with the addition of ultrasound‐assisted enzyme‐treated red lentil protein

Abstract: Summary The effects of red lentil protein with ultrasound‐assisted enzymatic treatment on the quality of brown rice noodles were investigated. The thermostability and anti‐retrogradation ability of brown rice flour decreased significantly (P < 0.05), while the elastic and viscous modulus increased after adding untreated red lentil protein. Meanwhile, the cooking loss rate of brown rice noodles increased from 4.41% to 5.68%. When the red lentil protein was treated with ultrasound and enzyme, the protein–starch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Proteolysis (EE) significantly reduced the α-helix structures (15.3%-4.2%), increased β-sheet structures (20.3%-33.5%) and did not change the unordered structures (48.7%-48.7%) compared to the AE extract. For lentil proteins, a similar reduction in αhelix structure was reported for Flavourzyme ® -treated red lentil proteins compared to the unhydrolyzed sample (22.5%-19.4%) (Lin et al, 2022). Additionally, the general trend that was observed in the present work (decrease in α-helix and increase in β-sheet structures) has been previously reported for hydrolyzed black bean and soy proteins (Chen et al, 2011;Yang et al, 2024;Zheng et al, 2019).…”
Section: Secondary Structure and Physicochemical Propertiessupporting
confidence: 89%
“…Proteolysis (EE) significantly reduced the α-helix structures (15.3%-4.2%), increased β-sheet structures (20.3%-33.5%) and did not change the unordered structures (48.7%-48.7%) compared to the AE extract. For lentil proteins, a similar reduction in αhelix structure was reported for Flavourzyme ® -treated red lentil proteins compared to the unhydrolyzed sample (22.5%-19.4%) (Lin et al, 2022). Additionally, the general trend that was observed in the present work (decrease in α-helix and increase in β-sheet structures) has been previously reported for hydrolyzed black bean and soy proteins (Chen et al, 2011;Yang et al, 2024;Zheng et al, 2019).…”
Section: Secondary Structure and Physicochemical Propertiessupporting
confidence: 89%
“…The lower digestibility values of the US sample combined with pH shift 2 were attributed to external factors that imbalanced denaturation-renaturation of the protein as renaturation resists digestion while denaturation facilitates digestion [110] . Lin, Liu [111] treated red lentil proteins with US alone (400 W and 20 min (ON 2 s/OFF 2 s)), enzyme (protease 1 % (w/w)) and combined US and enzyme and incorporated the treated proteins in brown rice noodles and evaluated the in vitro protein digestibility (IVPD) of the three noodle variants. The authors reported IVPD of 73.3, 78.6 and 80.4 % for noodles containing protein treated by US, enzyme and combined US and enzyme, respectively [111] .…”
Section: Impact Of Us On the Nutritional Profile Allergenicity And De...mentioning
confidence: 99%
“…Lin, Liu [111] treated red lentil proteins with US alone (400 W and 20 min (ON 2 s/OFF 2 s)), enzyme (protease 1 % (w/w)) and combined US and enzyme and incorporated the treated proteins in brown rice noodles and evaluated the in vitro protein digestibility (IVPD) of the three noodle variants. The authors reported IVPD of 73.3, 78.6 and 80.4 % for noodles containing protein treated by US, enzyme and combined US and enzyme, respectively [111] . This indicates a cumulative effect of the conformational changes caused by US and enzymatic protein hydrolysis that led to a considerable increase in the IVPD of the products.…”
Section: Impact Of Us On the Nutritional Profile Allergenicity And De...mentioning
confidence: 99%